FTA Strategy of Gaga Muhammad Post-Scandal: Image Recovery on Grace Tahir’s Podcast - Naifa Naila, Aisya; Putri, Arina; Ulfa, Maryam; Fransisca, Amanda; Rangkuti, Rahmadsyah; Irwan (Journal of Applied Linguistics, 2025)
This research explored the politeness strategies employed by Indonesian YouTube vloggers in response videos, focusing on a podcast discussion between Gaga Muhammad and Grace Thahir. Using a qualitative research design with a phenomenological approach, this study examines the interpersonal dynamics and the impact of face-threatening acts (FTAs) on public perception. Data were collected from a podcast episode of Voices of Change, where the two speakers discussed pressing social issues, community engagement, and mental health while also delving into Gaga's personal controversies, including his involvement in a fatal car accident. The analysis employed Brown and Levinson's politeness theory to identify strategies such as paying attention to the interlocutor's needs, exaggerating sympathy, avoiding conflict, and looking for consensus. Findings reveal that while Gaga uses politeness strategies to justify his actions and rebuild his public image, Grace frequently challenges his narrative through FTAs, targeting both his positive and negative face. For example, Grace confronts Gaga’s attempts at self-justification with direct critiques, often heightening the conversational tension. The podcast reflects societal expectations of public figures embroiled in scandals to exhibit remorse and take accountability. Despite efforts to apply positive politeness strategies, such as showing interest and declaring common ground, the discourse often shifts towards defensiveness, limiting its effectiveness in fostering mutual understanding. This study highlights the challenges of navigating public apologies and societal expectations, offering insights into the role of politeness in mitigating conflict and enhancing public discourse in social media interactions.   Keywords :     politeness strategies; face-threatening acts; YouTube vloggers; public discourse